When to start antiretroviral therapy: the need for an evidence base during early HIV infection - Lundgren, Jens D (BioMed Central, 2013)
BACKGROUND: Strategies for use of antiretroviral therapy (ART) have traditionally focused on providing treatment to persons who stand to benefit immediately from initiating the therapy. There is global consensus that any HIV+ person with CD4 counts less than 350 cells/μl should initiate ART. However, it remains controversial whether ART is indicated in asymptomatic HIV-infected persons with CD4 counts above 350 cells/μl, or whether it is more advisable to defer initiation until the CD4 count has dropped to 350 cells/μl. The question of when the best time is to initiate ART during early HIV infection has always been vigorously debated. The lack of an evidence base from randomized trials, in conjunction with varying degrees of therapeutic aggressiveness and optimism tempered by the risks of drug resistance and side effects, has resulted in divided expert opinion and inconsistencies among treatment guidelines. DISCUSSION: On the basis of recent data showing that early ART initiation reduces heterosexual HIV transmission, some countries are considering adopting a strategy of universal treatment of all HIV+ persons irrespective of their CD4 count and whether ART is of benefit to the individual or not, in order to reduce onward HIV transmission. Since ART has been found to be associated with both short-term and long-term toxicity, defining the benefit:risk ratio is the critical missing link in the discussion on earlier use of ART. For early ART initiation to be justified, this ratio must favor benefit over risk. An unfavorable ratio would argue against using early ART. SUMMARY: There is currently no evidence from randomized controlled trials to suggest that a strategy of initiating ART when the CD4 count is above 350 cells/μl (versus deferring initiation to around 350 cells/μl) results in benefit to the HIV+ person and data from observational studies are inconsistent. Large, clinical endpoint-driven randomized studies to determine the individual health benefits versus risks of earlier ART initiation are sorely needed. The counter-argument to this debate topic can be freely accessed here: http://www.biomedcentral.com/1741-7015/11/147.